2022
DOI: 10.3389/fonc.2021.797007
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 3D Structure, Cross Talks, and Prognostic Significance of KLF9 in Cervical Cancer

Abstract: Our study aimed to identify the new blood-based biomarkers for the diagnosis and prognosis of cervical cancer. Moreover, the three-dimensional (3D) structure of Kruppel-like factor 9 (KLF9) was also determined in order to better understand its function, and a signaling pathway was constructed to identity its upstream and downstream targets. In the current study, the co-expressions of tumor protein D52 (TPD52), KLF9, microRNA 223 (miR-223), and protein kinase C epsilon (PKCϵ) were evaluated in cervical cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Loss of KLF14 is reported to enhance the centrosome amplification through PLK4 that leads to carcinogenicity 13 . The expression loss of other KLFs, KLF3 and KLF9, was previously reported in breast cancer and cervical cancer 14 , 15 . Down-regulation of the transcription factor KLF14 is observed in colorectal cancer as well as several other human malignancies such as breast, lymphatic, cervical, oral cavity, floor of mouth, and pancreas 16 .…”
Section: Introductionmentioning
confidence: 60%
“…Loss of KLF14 is reported to enhance the centrosome amplification through PLK4 that leads to carcinogenicity 13 . The expression loss of other KLFs, KLF3 and KLF9, was previously reported in breast cancer and cervical cancer 14 , 15 . Down-regulation of the transcription factor KLF14 is observed in colorectal cancer as well as several other human malignancies such as breast, lymphatic, cervical, oral cavity, floor of mouth, and pancreas 16 .…”
Section: Introductionmentioning
confidence: 60%
“…Previous studies have shown that KLFs are critical mediators of cardiac development, hypertrophy, remodeling, injury repair, and electrical activity [ 29 ]. KLF9 is part of the KLFs family of members and has been reported to be associated with the progression of various cancers [ 30 ]. Additional studies have demonstrated multiple regulatory roles of KLF9 in the development of pathology.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported to be downregulated in various cancers, including endometrial carcinoma and colorectal cancer ( Kang et al, 2008 ; Simmen et al, 2008 ). Sadia et al discovered that KLF9 expression was significantly lower in cervical cancer patients compared to healthy controls and that it was significantly lower in the advanced tumor stage and distant metastatic groups compared to the lower tumor stage and non-metastatic groups ( Safi et al, 2021 ). However, Chen et al (2021b) discovered that KLF9 expression was positively associated with acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%